Asas Keseimbangan Dalam Perjanjian Kredit Benda Produktif (Grab Mobil) - Rachmatullah, Gaung Agung (Jurnal Restorative Justice, 2024)
The principle of balance is an important principle in contract law which aims to guarantee justice and equality of rights and obligations for the parties in an agreement, especially in credit agreements for productive objects such as Grab Mobil. Through this, driver partners obtain vehicles financed by financial institutions for productive purposes, but are often faced with terms and conditions that favor creditors. The emergence of this has the potential to cause injustice for driver partners who have a weak bargaining position. Based on articles in the Civil Code (Civil Code), the principle of balance directs contracts that are not only valid, but also pay attention to the principles of propriety and justice. In this discussion, analysis is carried out on the application of the principle of balance through three approaches: the statutory regulation approach to identify the legal basis; conceptual approach to understanding related legal theories; and approaches to studying the implementation of this principle in other legal systems. With this approach, the analysis is expected to provide a comprehensive picture regarding the application of balance in credit agreements for productive objects, in order to create a fair and appropriate agreement for all parties. The principles of pacta sunt servanda and freedom of contract also provide a strong legal basis for the application of the principle of balance. However, the application of the principle of balance in contract law in Indonesia still requires interpretive assessment, in contrast to countries such as the United States and England which have special regulations for measuring balance in consumer credit agreements. Through comparison with other countries, it appears that Indonesia can improve debtor protection with special regulations that ensure consumer rights are protected in credit agreements. Keywords: balance principle, credit agreement, productive objects.